Geochemical characteristics of basalts related to incipient oceanization: The example from the Alpine‐Tethys OCTs. (19th November 2019) - Amann, Méderic; Ulrich, Marc; Manatschal, Gianreto; Pelt, Eric; Epin, Marie‐Eva; Autin, Julia; Sauter, Daniel
Abstract: Basalts exposed in the Platta and Tasna nappes (SE Switzerland) derive from the Alpine‐Tethys ocean–continent transitions (OCT) and overlie subcontinental lithospheric mantle (SCLM). We show that the trace element signatures of these basalts differ from mid‐ocean ridge basalts (MORB). Two types of basalts occur in the OCT: a type‐1 showing a 'garnet signature' that can be modelled by the partial melting of the SCLM in the spinel stability field and a type‐2 characterized by an enrichment in incompatible elements that can be explained by the mixing between garnet‐pyroxenite‐derived melts and the melting of either a depleted MORB mantle or a refertilized SCLM. Based on the geological and geochemical observations, we propose that the basalts from the Alpine‐Tethys OCTs result from a poly‐phase magmatic system that carries an inherited SCLM signature. These basalts should therefore be referred to as OCT‐basalts rather than as MOR‐basalts.